Returning to School Following Hospitalization for Suicide-Related Behaviors: Recognizing Student Voices for Improving Practice. Issue 3 (3rd June 2022) - Marraccini, Marisa E.; Pittleman, Cari
Abstract: Adolescent hospitalizations for suicide-related behaviors have increased in recent years, with the highest rates occurring during the academic school year. Schools are a primary environment that adolescents return to following hospitalization, making them an important context for understanding recovery following a suicidal crisis. Although previous research highlights provider perceptions for improving this transition, limited research has focused on adolescent views. This qualitative study presents findings from interviews with 19 adolescents previously hospitalized for a suicide-related crisis. Results highlight the need to strengthen social supports for returning youth. Specifically, findings suggest the importance of emotional supports (e.g., positive school relationships and a safer psychosocial school climate), instrumental supports (e.g., collaborations and communication around reentry), informational supports (clearer procedures for academics and reentry processes), and appraisal supports that acknowledge the complexity of adolescent functioning upon return. Findings reinforce the importance of the school psychologist's role in partnering with returning youth and their families and providing consultation to other school professionals about supporting their recovery. Impact Statement This study elevates adolescent voices by describing their experiences and viewpoints regarding school reintegration following psychiatric hospitalization for suicide-related behaviors. School psychologists and other school professionals should partner with returning students and families in supporting reintegration, and collaborate to strengthen student–adult relationships upon their return. While standard protocols for supporting returning adolescents may help improve reentry processes overall, it remains of critical importance to tailor safety plans and reentry plans based on individual adolescent experiences.